Analysis of MTR rs1805087 A2756G in non-syndromic cleft lip and palate and MTHFD1 rs2236225 G1958A in non-syndromic cleft palate among Indonesian Deutero-Malay population - Saskia Lenggogeni Nasroen; Puteri Alvi Khoirianisa Sujaya; Nabila Ulul Azmi Ramadhani; Jeffrey; Rudi Satria Darwis (Dental Journal (Majalah Kedokteran Gigi), 2026)
Background: Non-syndromic cleft lip and palate (NS CLP) and non-syndromic cleft palate (NS CP) are abnormalities arising from palate and lip fusion failure, which begins in the sixth week of pregnancy and is caused by multifactorial (genetic and environmental) factors. Methionine Synthase (MTR) rs1805087 A2756G and Methylenetetrahydrofolate Dehydrogenase, Cyclohydrolase, and Formyltetrahydrofolate Synthetase 1 (MTHFD1) rs2236225 G1958A are two genes suspected of being risk factors for NS CLP and NS CP, but they have not been studied in the Indonesian population. Purpose: This study aims to determine the risk factors for NS CLP and NS CP disorders in the Indonesian Deutero-Malay population. Methods: The results were obtained by analyzing the MTR rs1805087 A2756G (67 control and 35 NS CLP patients) and MTHFD1 rs2236225 G1958A (52 control and 49 NS CP patients) polymorphisms using the Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLPs) method. Results: This study found no polymorphism among all MTR rs1805087 A2756G participants. As for the MTHFD1 rs2236225 G1958A gene, there were no significant results found, but the A mutant allele (OR=0.613, p=0.115) and the AA mutant homozygote genotype (OR=0.521, p=1.000) appear to be protective factors. Conclusion: This study concluded that MTR rs1805087 A2756G and MTHFD1 rs2236225 G1958A are not risk factors for NS CLP and NS CP in the Indonesian Deutero-Malay population.